Oscillations in linear difference equations with variable coefficients. (1991) - Philos, Ch. G.; Purnaras, I. K.
Abstract : A class of linear difference equations with variable coefficients is considered. Sufficient conditions and necessary conditions for the oscillation of the solutions are established. In the special cases where the coefficients are constant or periodic the conditions become both necessary and sufficient.